The safety of biological preparations. Part 2. Safety issues of biosimilars - A. A. Soldatov; Zh. I. Avdeeva; Yu. V. Olefir; V. A. Merkulov; V. P. Bondarev (Биопрепараты: Профилактика, диагностика, лечение, 2018)
The use of the reduced scheme in preclinical and clinical studies of «biosimilars» requires special attention to the safety issues. During the process of the marketing authorization of biosimilars in 2013-2015 the countries with advanced regulatory and pharmacovigilance systems (USA, Canada and EU countries), the most contentious debates were provoked by the issues of extrapolation of the results of the research of a biosimilar infliximab (TNFα-specific monoclonal antibodies). EMA made the decision that the results of the efficacy and safety studies of infliximab, obtained in adult patients with rheumatoid disease, can be extrapolated to the indications for the treatment of inflammatory bowel disease (Crohn’s disease and ulcerative colitis in adults and in children). Several medical associations such as the Association of Gastroenterologists and the Association of Pediatricians believe that this extrapolation is not justified. Health Canada also made a conclusion that the extrapolation is not justified and did not approve the use of the mentioned preparation for the treatment of Crohn’s disease and ulcerative colitis. There is still an ongoing hot discussion on the issue of interchangeability of an original medicine and a biosimilar. Given that the safety of a biosimilar has been studied before obtaining marketing authorization not to the fullest extent, usually safety studies continue after obtaining marketing authorization for a few more years. If there is an interchange of medicines, then it is not possible to objectively evaluate the safety of a biosimilar. In the countries with poor regulatory and pharmacovigilance system not only «biosimilars» are in drug circulation system, but also other medicines registered under the reduced studies scheme, but not in full compliance with the principles of «biosimilarity». The quality of these medicines does not always meet the standards, as evidenced by numerous studies. WHO is concerned about the quality of the mentioned medicines and suggests to call them «non-innovators» and establish a separate group, and claimed that the sponsors were invited for a certain period of time to provide the evidence of the high quality of these medicines.